Enhancement of Photocatalytic Activity of Bi2O3–BiOI Composite Nanosheets through Vacancy Engineering. Issue 23 (24th April 2019) - Bai, Jinwu; Li, Yun; Wei, Pengkun; Liu, Jiandang; Chen, Wei; Liu, Lu
Abstract: Vacancy engineering is an effective strategy to enhance solar‐driven photocatalytic performance of semiconductors. It is highly desirable to improve the photocatalytic performance of composite nanomaterials by the introduction of vacancies, but the role of vacancies and the heterostructure in the photocatalytic process is elusive to the composite nanomaterials. Herein, the introduction of I vacancies can significantly enhance the photocatalytic activity of Bi2 O3 –BiOI composite nanosheets in a synergistic manner. The excellent photocatalytic performance of the Bi2 O3 –BiOI composites is attributed to the combination of Bi2 O3 and BiOI and the existence of I vacancies in Bi2 O3 –BiOI composites. Specifically, density functional theory calculation shows that the existence of I vacancies would create a new electric states vacancy band below the conduction band of BiOI and thus can reduce the bandgap of BiOI nanosheets. This greatly facilitates the scavenging of the photogenerated electron on the surface of BiOI by Bi2 O3, therefore, enhancing the overall photocatalytic activity of the composites. The enhanced photocatalytic efficiency is demonstrated by the degradation of tetracycline (TC), which reaches 96% after 180 min and by the high total organic carbon (TOC) removal (89% after 10 h visible light irradiation). This study provides a novel approach for the design of high‐performance composite catalysts. Abstract : The photocatalytic performance of BiOI nanosheets is obviously improved by the introduction of vacancies and the formation of heterojunction structures. Compared to that of BiOI nanosheets, Bi2 O3 –BiOI composites exhibit excellent photodegradation efficiency for tetracycline, which is about 96% after 180 min and the total organic carbon (TOC) removal efficiency achieves about 89% after 10 h visible light irradiation.